Efficacy of lenvatinib combined with sequential transarterial chemoembolization for primary hepatocellular carcinoma and the effects on serum basic fibroblast growth factor and vascular endothelial growth factor - Xie, Qing-Yun; Huang, Lu-Ping; Gao, Feng-Wei; Liu, Da-Qing; Wang, Xia; Jiang, Kang-Yi; Gong, Jie; Zhao, Xin; Gao, Ben-Jian; Lei, Ze-Hua (Frontiers in Pharmacology, 2022)
Objective: The aim of this research was to investigate the therapeutic efficacy of lenvatinib combined with sequential TACE on primary HCC and the effects on serum bFGF and VEGF. Method: A total of 104 patients with primary HCC, admitted to People’s Hospital of Leshan from April 2018 to January 2021, were selected as the study subjects and were divided into the TACE-LEN group (n=53) who were treated with lenvatinib combined with sequential TACE and the TACE group (n=51) who were treated with TACE alone, according to the appropriate treatment modalities. The clinical efficacy eight weeks after treatment; the serum levels of total bilirubin, conjugated bilirubin, and alanine aminotransferase (ALT); the prothrombin time (PT); the indocyanine green retention rate at 15 min (ICGR15); and the serum bFGF and VEGF levels before treatment and at eight weeks after treatment were compared between the two groups. The incidence of adverse events and the survival rates at 18 months were also recorded for both groups. COX regression analysis was used to analyze the risk factors affecting the survival of patients. Results: Eight weeks after treatment, the objective response rate was higher in the TACE-LEN group than in the TACE group (77.36% vs 56.36%, P<0.05), but there were no statistically significant differences in the bilirubin and ALT levels, the PT, and the ICGR15 between the two groups (P>0.05). The serum bFGF and VEGF levels post- therapeutic were lower in the TACE-LEN group than in the TACE group (P<0.05). The differences in the incidence of postoperative adverse events and the survival rate within six months were not statistically significant between the two groups (P > 0.05). In addition, the survival rates within 12 and 18 months after treatment were higher in the TACE-LEN group than in the TACE group than in the TACE group (81.1% vs64.7% , 69.8%vs49.1%, P<0.05). ICG-R15 and treatment regimen are risk factors for survival. Conclusion: The worse the liver reserve is, the worse the prognosis is. The combination of TACE and lenvatinib showed better efficacy and longer survival than TACE monotherapy for HCC patients and reduced the levels of bFGF and VEGF.